Management of preterm severe preeclampsia: interventional versus expectant management - Durairaj, Anitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Management of preterm severe preeclampsia is challenging. This study aims to determine the maternal and perinatal outcomes in interventional and expectant management. Methods: This was a prospective study conducted at Institute of obstetrics and gynecology, Chennai over a period of three years. Patients with preterm severe preeclampsia of gestational age 28 weeks to 31 weeks and 6 days who had interventional and expectant management were recruited. Clinical details relevant to maternal, fetal and neonatal outcome were collected and the data were analyzed using IBM.SPSS statistics software 23.0 Version. Results: Termination of pregnancy in the expectant management was done mostly for maternal indications (66%). The mean prolongation of pregnancy in the expectant management was 7.67 days and it was statistically significant. Though maternal complications were slightly higher with the expectant management, but it was not statistically significant. Early neonatal death, perinatal death and mean NICU stay were lower in the expectant management with statistical significance. Mean gestational age at delivery, mean birth weight and neonatal survival rate were statistically significantly higher in the expectant management than the interventional management. Conclusions: Optimizing maternal and perinatal outcome is the key in the management of preterm severe preeclampsia. Expectant management of preterm severe preeclampsia results in a better obstetric outcome and should be done only in well selected patients in a tertiary care centre.